Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1590/1676-0611-bn-2014-0179
|View full text |Cite
|
Sign up to set email alerts
|

Purification and physico-chemical study of serum albumins of two neotropical fish species from the São Francisco River Bassin, Brazil

Abstract: This paper presents results from a study of albumin from pacu (Piaractus mesopotamicus, Holmberg 1887) and the catfish pintado (Pseudoplatystoma corruscans, Spix & Agassiz, 1829), two neotropical fish species inhabitants of Brazilian rivers, comparing their molecular mass and discussing their secondary structures based on spectropolarimetric (circular dychroism) measurements. Genetic controlled specimens were obtained from two fish hatcheries, located in Mococa (pacu) and in São João da Boa Vista (pintado)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It has been shown that total plasma protein and albumin content of mammalian serum is twice and four times that of fish respectively [ 52 ]. Though variable, lower values of albumin and plasma protein when compared to mammals have been consistently shown in sera from fish species [ 21 , 24 , 42 ]. Thus, V. anguillarum may be better able to grow at lower concentrations of FBS as this would be comparable to both its native marine environment and the blood of potential teleostean host species.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that total plasma protein and albumin content of mammalian serum is twice and four times that of fish respectively [ 52 ]. Though variable, lower values of albumin and plasma protein when compared to mammals have been consistently shown in sera from fish species [ 21 , 24 , 42 ]. Thus, V. anguillarum may be better able to grow at lower concentrations of FBS as this would be comparable to both its native marine environment and the blood of potential teleostean host species.…”
Section: Discussionmentioning
confidence: 99%